Khazanah Passenger’s Utterence Train Department of Malang — Bandung (Sosiopragmatic Study) - Sofia Eka Kurniasari; Vrestanti Novalia Santosa (IKIP Budi Utomo Malang, 2020)
This research aims to (1) describe code-switching utterences of train passenger’s Malang-Bandung, (2)describe the meaning of utterences of train passenger’s Malang-Bandung, (3) describe the effect of utterances of train passenger’s Malang-Bandung. This type of the research is a descriptive qualitative research. The research methodeused case study that lead to phenomenology approach. The subjects of of the research are the train passengers with form of utterences. The technique used of collecting data are SBLC, record, notes, and documentation technique.The instrument are notes, recording devices containing audio, visual, and audio-visual. The result of the research is a khazanah of utterences of train pasengers Malang-Bandung route with some factors that being background of code-switching occurred. This research uses siciopragmatic in analyzing the data to find the meaning of the utterence on the use of language in certtain cultural societies and social conditions. The result of the research included (1) the speech form of code-switching the train passengger’s for Malang—Bandung that was part of the intern and ekstern code, (2) the official meaning utterences code-switching of train pasengger’s Malang—Bandung, and (3) factors that affected the code-switching of train passengger’s Malang—Bandung.